Iron Age Settlement at Blackstone, Worcestershire: Excavations 1972, 1973, and 1977 - Derek Hurst; Alan Hunt; Peter Davenport (Internet Archaeology, 2010)
Aerial photography in 1957 resulted in the discovery of a rectangular double-ditched enclosure overlooking the Severn floodplain near Bewdley, Worcestershire (UK). Excavation in the 1970s, in advance of gravel extraction, provided limited evidence of Mesolithic, Neolithic and Bronze Age activity prior to occupation in the later Iron Age, when the enclosure was established. This comprised a ditch and bank, and later a palisade and ditch, with single and double portal gateways respectively, and with buildings internally. Pottery and briquetage indicate trading links with the wider region, respectively with west and north Worcestershire, and with Droitwich. The main Iron Age occupation is dated from the 2nd century into the 1st century BC.